Non-steroidal FXR agonist cilofexor improves cholestatic liver injury in the Mdr2-/- mouse model of sclerosing cholangitis - Claudia D. Fuchs; Natalie Sroda; Hubert Scharnagl; Ruchi Gupta; Wesley Minto; Tatjana Stojakovic; John T. Liles; Grant Budas; David Hollenback; Michael Trauner (JHEP Reports, 2023)
Background & Aims: The nuclear receptor farnesoid X receptor (FXR) is a key regulator of hepatic bile acid (BA) and lipid metabolism, inflammation and fibrosis. Here, we aimed to explore the potential of cilofexor (GS-9674), a non-steroidal FXR agonist, as a therapeutic approach for counteracting features of cholestatic liver injury by evaluating its efficacy and mechanisms in the Mdr2/Abcb4 knockout (-/-) mouse model of sclerosing cholangitis. Methods: FVB/N wild-type and Mdr2-/- or BALB/c wild-type and Mdr2-/- mice were treated with 0, 10, 30 or 90 mg/kg cilofexor by gavage every 24 h for 10 weeks. Serum biochemistry, gene expression profile, hydroxyproline content, and picrosirius red and F4/80 immunostaining, were investigated. Bile flow, biliary bicarbonate and BA output, and hepatic BA profile, were assessed. Results: Cilofexor treatment improved serum levels of aspartate aminotransferase, alkaline phosphatase as well as BAs in Mdr2-/- animals. Hepatic fibrosis was improved, as reflected by the reduced picrosirius red-positive area and hydroxyproline content in liver sections of cilofexor-treated Mdr2-/- mice. Intrahepatic BA concentrations were lowered in cilofexor-treated Mdr2-/- mice, while hepatobiliary bile flow and bicarbonate output were increased. Conclusion: Collectively the current data show that cilofexor treatment improves cholestatic liver injury and decreases hepatic fibrosis in the Mdr2-/- mouse model of sclerosing cholangitis. Impact and implications: Treatment with cilofexor, a non-steroidal farnesoid X receptor (FXR) agonist, improved histological features of sclerosing cholangitis, cholestasis and hepatic fibrosis in the Mdr2-/- mouse model. These findings indicate, that pharmacological stimulation of intestinal FXR-mediated gut-liver signaling, via fibroblast growth factor 15 (thereby reducing bile acid synthesis), may be sufficient to attenuate cholestatic liver injury in the Mdr2-/- mouse model of sclerosing cholangitis, thus arguing for potential therapeutic properties of cilofexor in cholestatic liver diseases.